Internationalisation and Globalisation in Mathematics and Science Education
XXVII, 542 p.
Keywords: In the new times of globalisation, international academic contacts and collaborations are ever increasing. They are taking many forms, from international conferences and publications, student and academic exchange, cross cultural research projects, curriculum development to professional development activities and affect every aspect of academic life from teaching, research to service. This book aims to: Develop theoretical frameworks of the phenomena of internationalisation and globalisation and identify related ethical, moral, political and economic issues facing mathematics and science educators. Provide a venue for the publication of results of international comparisons on cultural differences and similarities rather than merely on achievement and outcomes. Provide a forum for critical discussion of the various models and forms of international projects and collaborations. Provide a representation of the different voices and interests from around the world rather than consensus on issues.